Women’s role as constructive agents in the economic reconstruction in post–conflict period - Menaka, R.A.H. (University of Jaffna, 2012)
When we talk about post conflict reconstructions women must be involved, because they have important and necessary roles to play in all the phases of post conflict reconstruction. Arm conflict affected the women and men differently. Following the death, disappearance or detention or permanent or temporary disability of the male family member or loss of documents made to deprived of their sole means of income and are struggling to meet their daily basic house hold needs. Armed conflict creates large number of households headed by women. A large number of conflict affected women has no independent means of income as they have relied economically on male family members. As a result women are generally responsible for running the house–holds. Moreover mental pain and suffering because individual was deprived of all economic resources. Now women are economic actors, and important in post-conflict period. But legal and social norms restrict their role in Economic right and fail to encourage their capacity development. Accordingly law makers and the state have great responsibility to reconstruct women’s lives and their future. Because during the war period women have lost lives, property and also documentary evidence of entitlements and relationships as a result of war. Internal conflicts and wars have led to displacement and destruction of property and livelihoods, which place women in an ever more vulnerable position. To understand the role that women should play in post conflict situation is largely situated in the roles they played before and during the conflict. In present situation laws of the country did not recognize their rights special in economic sector. Due to this women are helpless. In post conflict period only legal structure and the laws can provide reliefs to women. Accordingly this article will discuss about how the law can encourage women in their capacity development in post conflict period.